Vector and virus induce plant responses that benefit a non-vector herbivore - Belliure, Belén; Sabelis, Maurice W.; Janssen, Arne (2017)
The negative cross-talk between induced plant defences against pathogens and arthropod herbivores is exploited by vectors of plant pathogens: a plant challenged by pathogens reduces investment in defences that would otherwise be elicited by herbivores. This negative cross-talk may also be exploited by non-vector herbivores which elicit similar anti-herbivore defences in the plant. We studied how damage by the thrips Frankliniella occidentalis and/or infection with Tomato spotted wilt virus (TSWV) affect the performance of a non-vector arthropod: the two-spotted spider mite Tetranychus urticae, a parenchym feeder just like F occidentalis. Juvenile survival of spider mites on plants inoculated with TSWV by thrips was higher than on control and on thrips-damaged plants. However, thrips damage did not reduce spider-mite survival as compared to the control, suggesting that the positive effect of TSWV on spider-mite survival is independent of anti-thrips defence. Developmental and oviposition rates were enhanced on plants inoculated with TSWV by thrips and on plants with thrips damage. Therefore, spider mites benefit from TSWV-infection of pepper plants, but also from the response of plants to thrips damage. We suggest that the positive effects of TSWV on this non-vector species cannot be explained exclusively by cross-talk between anti-herbivore and anti-pathogen plant defences.